Strike-Slip Transpressional Uplift Offshore San Onofre, California Inhibits Sediment Delivery to the Deep Sea - Wei, Emily A.; Holmes, James J.; Driscoll, Neal W. (Frontiers in Earth Science, 2020)
The Inner California Borderlands is a complex margin where sediment delivery to the basin floor is largely routed through canyon-channel-gully systems. Using nested geophysical surveys, piston and gravity cores from the Eastern Gulf of Santa Catalina, this study compares two canyon systems and investigates how tectonics, shelf width, gradient, and autogenic processes influence turbidite emplacement timing and grain size. One end-member canyon is the Dana Point Canyon, which is ~2 km from the San Juan Creek drainage and has a concave-up channel profile. The other endmember system consists of the San Onofre North and South (SON and SOS) canyons that are detached from San Mateo Creek by a wide 10 km shelf and they traverse a tectonically-deformed slope with multiple ponded basins. Radiocarbon ages sampled from 8 cores reveal that turbidite deposition at Dana Point persists during the sea-level lowstand of Marine Isotope Stage (MIS) 2 through the subsequent transgression and highstand. On the contrary, turbidite emplacement adjacent to the SON and SOS canyons occurs mostly during MIS 2 and ceases around 8 ka. The main regional control on turbidite timing is the wide shelf adjacent to the SON and SOS canyons that is formed by a broad uplifted anticline. This anticline separates the SON and SOS canyons from a riverine source during the sea-level transgression. Much of the tectonic deformation offshore of San Onofre was created by transpression along the right-lateral Newport Inglewood-Rose Canyon Fault Zone. Second-order controls on local turbidite emplacement include small synclines and anticlines that form ponded basins and accommodate deformation on the San Mateo Fault Zone. These basins engender deposition and intervening steep slopes promote sediment bypass. Complex bathymetry offshore San Onofre also affects channel gradient by either accelerating or decelerating flow. Turbidity flow dynamics modified by gradient changes offshore of San Onofre have the ability to modulate channel architecture and grain size. The implications of this work are that tectonically-deformed morphology complicates the timing of turbidite emplacement throughout a sea level cycle and the interpretation of turbidites as paleoseismic records in such regions.